LINC-PINT regulated the migration and epithelial-mesenchymal transition of HK-2 cells treated with high glucose by targeting miR-1297 - Ying Xi-hui; Liao Jian; Ju Mei; Huang Xiao-yan; Li Juan (Linchuang shenzangbing zazhi)
ObjectiveTo explore the effect of long intergenic non-protein coding RNA-p53 induced transcript （LINC-PINT） on the migration and epithelial-mesenchymal transition （EMT） of human renal tubular epithelial HK-2 cells treated with high glucose （HG） and elucidate its molecular mechanism.MethodsHK-2 cells were treated with 5.5 and 30 mmol/L glucose and recorded as NG and HG groups. HK-2 cells in HG group were divided into the groups of HG+si-NC， HG+si-LINC-PINT， HG+miR-NC， HG+miR-1297， HG+si-LINC-PINT+anti-miR-NC and HG+si-LINC-PINT+anti-miR-1297. Reverse transcription-quantitative polymerase chain reaction （RT-qPCR） was used for detecting the expression levels of LINC-PINT and miR-1297. Transwell and Western blot for detecting the migration of HK-2 cells and the expression of related proteins. Dual luciferase reporter assay for examining the targeting relationship between LINC-PINT and miR-1297.ResultsCompared with NG group， the expression levels of LINC-PINT ［（1.00±0.05） vs （2.87±0.19）］ and miR-1297 ［（1.02±0.07） vs （0.43±0.04）］ significantly spiked and dropped obviously in HG group； number of migrated cells ［（89.37±4.56） vs （212.35±13.28）］ and expression levels of MMP-2 ［（0.31±0.02） vs （0.79±0.07）］， vimentin ［（0.22±0.01） vs （0.58±0.03）］， α-SMA ［（0.19±0.02） vs （0.53±0.05）］ and FN ［（0.12±0.01） vs （0.34±0.04）］ rose obviously while expression level of E-cadherin declined markedly ［（0.69±0.07） vs （0.27±0.02）， P<0.05］. Suppression of LINC-PINT expression or over-expression of miR-1297 significantly lowered the number of migrated cells ［（197.28±10.25） vs （137.53±7.59）， （216.58±13.87） vs （145.29±6.82）］ and the expression levels of MMP-2 ［（0.83±0.05） vs （0.47±0.04）， （0.78±0.05） vs （0.42±0.04）］， vimentin ［（0.62±0.05） vs （0.36±0.02）， （0.56±0.04） vs （0.32±0.03）］， α-SMA［（0.51±0.03） vs （0.28±0.02）， （0.56±0.03） vs （0.30±0.02）］ and Fn ［（0.37±0.03） vs （0.23±0.03）， （0.36±0.03） vs （0.25±0.02）］ and significantly boosted the expression level of E-cadherin ［（0.24±0.02） vs （0.58±0.03）， （0.23±0.02） vs （0.55±0.04）］（P<0.05）. LINC-PINT targeted the expression of miR-1297 （P<0.05）. A down-regulation of miR-1297 reversed the effect of suppressing the expression of LINC-PINT on the migration and EMT of HK-2 cells treated with HG （P<0.05）.ConclusionLINC-PINT regulates the migration and EMT of HK-2 cells treated with HG through targeting miR-1297.